2018
DOI: 10.1200/jco.2017.76.0355
|View full text |Cite|
|
Sign up to set email alerts
|

Three Versus 6 Months of Oxaliplatin-Based Adjuvant Chemotherapy for Patients With Stage III Colon Cancer: Disease-Free Survival Results From a Randomized, Open-Label, International Duration Evaluation of Adjuvant (IDEA) France, Phase III Trial

Abstract: Purpose Reduction of adjuvant treatment duration may decrease toxicities without loss of efficacy in stage III colon cancer. This could offer clear advantages to patients and health care providers. Methods In International Duration Evaluation of Adjuvant Chemotherapy (IDEA) France, as part of the IDEA international collaboration, patient with colon cancer patients were randomly assigned to 3 and 6 months of modified FOLFOX6 (mFOLFOX6: infusional fluorouracil, leucovorin, and oxaliplatin) or capecitabine plus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 21 publications
7
114
0
3
Order By: Relevance
“…Patients with T4 category have by far the worst survival rate regardless of stage II or III disease, 36 and adequate duration of adjuvant chemotherapy is recommended to these patients. 37,38 Consistent with previous observations, [36][37][38][39] our study also found that the 5-year OS rate of patients with T4 category or shorter chemotherapy duration was approximately 60%, whereas the 5-year OS rate of patients with T1-3 category or longer chemotherapy duration was approximately 80%. In the subgroup analyses, CIK cell immunotherapy was found to be significantly associated with an improved DFS and OS in patients with T4 category or shorter chemotherapy duration, but this association was absent in patients with T1-3 category or longer chemotherapy duration.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with T4 category have by far the worst survival rate regardless of stage II or III disease, 36 and adequate duration of adjuvant chemotherapy is recommended to these patients. 37,38 Consistent with previous observations, [36][37][38][39] our study also found that the 5-year OS rate of patients with T4 category or shorter chemotherapy duration was approximately 60%, whereas the 5-year OS rate of patients with T1-3 category or longer chemotherapy duration was approximately 80%. In the subgroup analyses, CIK cell immunotherapy was found to be significantly associated with an improved DFS and OS in patients with T4 category or shorter chemotherapy duration, but this association was absent in patients with T1-3 category or longer chemotherapy duration.…”
Section: Discussionsupporting
confidence: 91%
“…[18,19] The most common side effect from oxaliplatin is peripheral neuropathy, and the risk increases with cumulative doses. [18,19,[62][63][64] These symptoms can occur shortly after oxaliplatin administration and appear as symptoms such as numbness/tingling in the fingers, toes, or pharynx, and increased sensitivity to cold exposure. Neurotoxicity is a common dose-limiting toxicity of oxaliplatin.…”
Section: Symptoms and Signs In Colorectal Cancer Patientsmentioning
confidence: 99%
“…Our ndings from population-based cancer registry data con rmed that higher chemotherapy RDI was needed in high-risk stage III colon cancers, compared with low-risk cancers, and are consistent with the conclusions from six randomized, phase 3 clinical trials conducted by the International Duration Evaluation of Adjuvant Therapy (IDEA) collaboration, which found that 6 months of FOLFOX particularly bene ted high-risk stage III colon cancers. These clinical trials evaluated whether 3 months of FOLFOX or CAPOX is non-inferior to 6 months of therapy in the rate of disease-free survival at 3 years [4,9,32,33]. Results from a pooled analysis of six trials showed that in stage III colon cancer patients treated with FOLFOX, 6-month therapy had a higher rate of disease-free survival than 3-month therapy, particularly in the high-risk group [9].…”
Section: Discussionmentioning
confidence: 99%
“…Results from a pooled analysis of six trials showed that in stage III colon cancer patients treated with FOLFOX, 6-month therapy had a higher rate of disease-free survival than 3-month therapy, particularly in the high-risk group [9]. Data from the IDEA France suggested that for FOLFOX6 regimen, patients with high-risk stage III colon cancer need 6-month chemotherapy for a maximal relapse risk reduction, for lowrisk cancer patients, the absolute difference in the 3-year disease free survival rate between 6 and 3 months of chemotherapy was clinically less relevant (2%) [33]. Older clinical trials have also shown that the e cacy of oxaliplatin is more signi cant in stage III N2 tumors, compared to stage III N1 tumors [34,35] (10-year overall survival advantage of 12.9% (p=0.013) in those with N2 tumors, and 6% (p=0.248) in those with N1 tumors, when adding oxaliplatin to 5-FU plus leucovorin [35]).…”
Section: Discussionmentioning
confidence: 99%